Experiences with Internships: Perceptions of Undergraduate Publishing Students at the Kwame Nkrumah University of Science and Technology, Ghana - Michael Ato Essuman; Elijah Afeliga (E-Journal of Humanities, Arts and Social Sciences)
The Industrial internship is the platform that enables students to experience the practical aspects of what they learn outside the classroom. The internship is a facilitator that allows students to put into practice what they have learned in school. The study assessed students’ opinions of their internship experience to identify the strengths and weaknesses of the system. Data were collected from 160 students from the Publishing Department. The survey instrument used to gather information and data from the respondents was a well-structured questionnaire consisting of 37 test items. The students responded to the questionnaire using Google Forms, which were sent to the sampled students. Data were analysed using descriptive statistics. The results of the study showed that most of the interns felt that the courses they took on campus before the internship improved their understanding of the issues they encountered at the workplace during the internship. Most respondents believed that industrial placement improves interns’ career choices. The respondents recommended that the University reviews the staff visit times at the companies where students undertake their internships. Respondents also cited financial challenges as the biggest problem during the internship programme. Students enjoyed completing internships in industry, and believe that it will enhance their career goals and job opportunities. The study presents a clear road map to strengthen the Student Internship programme and contribute immensely to the industry’s growth. Also, the publishing industry can leverage on the findings to improve its internship policy.